Problem-Based Learning On The Ability Of Concept Understanding And Problem Solving Students' Mathematics On Function Material Squares In Grade X - Pardosi, Monalisa; Tambunan, Hardi; Sitepu, Christina P (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the effect of problem-based learning on students' conceptual understanding and mathematical problem solving abilities on quadratic function material at SMK Negeri 5 Medan 2024/2025. The type of research used is quantitative descriptive. The research population was all class X, and the research sample consisted of 65 class X students. The sampling technique was carried out using purposive sampling technique. The instruments used were tests, questionnaires and observation sheets. Hypothesis testing in this study used t-test and descriptive test. The results of the study showed that: (1) problem-based learning has an effect on conceptual understanding abilities, (2) the magnitude of the influence of problem-based learning on students' conceptual understanding abilities is 89.2%, (3) problem-based learning has an effect on mathematical problem solving abilities, (4) the magnitude of the influence of problem-based learning on problem solving abilities is 69.0%, (5) problem-based learning on students' conceptual understanding abilities is effective, (6) problem-based learning on problem solving abilities are effective.